مدى إلتزام مديري المدارس في فلسطين بأخلاقيات المهنة : دراسة ميدانية في مدارس محافظة رام الله والبيرة - شعيبات، محمد عوض; عطيوي، فاطمة خليل; أبوسمرة، محمود أحمد (جامعة الكويت - مجلس النشر العلمي, 2016)
This study aims at identifying to what extent school principals in Palestine are committed to school administration ethics from their teachers’ perspectives. The study population consisted of all (4430) male and female school teachers in "Ramallah and El Beira" governorate. A stratified random sample was selected of (440) teachers, (10% of the study population). The researchers used a questionnaire to collect data. The questionnaire included (45) items distributed on four aspects. Validity and reliability were examined via appropriate statistical methods. The results revealed that teachers’ evaluation for principals’ commitment of school administration ethics on the total score took a high degree with a mean of (3.91). The study results also showed that there are no statistically significant differences for the commitment of the school principals of school administration ethics from teachers’ perspectives due to the gender and qualification variables, while there are statistically significant differences due to the variables: years of experience and supervising authority. A number of recommendations are cited.
هدفت هذه الدراسة التعرف إلى مدى التزام مديري المدارس في فلسطين بأخلاقيات المهنة من وجهة نظر المعلمين، وجاءت هذه الدراسة كدراسة ميدانية على مدارس محافظة "رام الله والبيرة"، وتكون مجتمع الدراسة من جميع معلمي مدارس محافظة "رام الله والبيرة" البالغ عددهم (4430) معلماً ومعلمة، وتم اختيار عينة طبقية عشوائية مكونة من (440) معلماً ومعلمة. وقام الباحثون ببناء استبانة أداة للدراسة، تضمنت (53) فقرة موزعة على أربعة مجالات، وتم التحقق من صدقها وثباتها بالطرق الإحصائية المناسبة. وأظهرت نتائج الدراسة أن تقديرات المعلمين لمدى التزام مديري المدارس بأخلاقيات المهنة جاءت بدرجة مرتفعة، وبمتوسط حسابي (3.91)، كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية بين تقديرات أفراد عينة الدراسة لمدى التزام مديري المدارس بأخلاقيات المهنة تعزى لمتغيري الجنس، والمؤهل العلمي، ووجود فروق ذات دلالة إحصائية تعزى لمتغيري سنوات الخبرة، لصالح الخبرة الأقل من 5 سنوات، ولمتغير الجهة المشرفة على المدرسة، لصالح مدارس الحكومة والخاصة. وفي ضوء نتائج الدراسة أوصى الباحثون بعدد من التوصيات.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- المؤسسات التعليمية -- الأخلاق المهنية -- فلسطين -- القدس -- رام الله